\(\frac{24}{9}-\left(x+\frac{1}{2}\right)^2=2\frac{1}{3}\)
\(\Rightarrow\frac{24}{9}-\left(x+\frac{1}{2}\right)^2=\frac{7}{3}\)
\(\Rightarrow\left(x+\frac{1}{2}\right)^2=\frac{24}{9}-\frac{7}{3}\)
\(\Rightarrow\left(x+\frac{1}{2}\right)^2=\frac{24}{9}-\frac{21}{9}\)
\(\Rightarrow\left(x+\frac{1}{2}\right)^2=\frac{3}{9}=\frac{1}{3}\)
Ta thấy: \(\frac{1}{3}\)không là SCP
\(\Rightarrow x=\varnothing\)
Vậy không tìm được x thỏa mãn
\(\frac{24}{9}-\left(x+\frac{1}{2}\right)^2=2\frac{1}{3}\)
\(\frac{8}{3}-\left(x+\frac{1}{2}\right)^2=\frac{7}{3}\)
\(\left(x+\frac{1}{2}\right)^2=\frac{8}{3}-\frac{7}{3}=\frac{1}{3}\)
Mà \(\frac{1}{3}\)không là số chính phương
=> không có x nào thỏa mãn bài trên